2003
DOI: 10.1046/j.0175-8659.2003.00498.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of peat substrate on the distribution and behaviour patterns of sand shrimp, Crangon septemspinosa , under experimental conditions

Abstract: Peat harvesting is a lucrative industry in New Brunswick, Canada, and is for the most part located along the coast. Current methods of mining peatlands are such that high levels of peat fibers are transported by runoff into fresh and marine waters. To understand better the influence of peat substrate on aquatic organisms living in peat-impacted habitats, the sand shrimp (Crangon septemspinosa) was used as a bioindicator. A series of laboratory experiments was conducted in which shrimp were provided with a choi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0
3

Year Published

2006
2006
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 27 publications
3
15
0
3
Order By: Relevance
“…Even though these animals live in a different environment and consequently differ physiologically from the species studied in this present study, both results confirm the statement by Dall et al (1990) that substrates with particles between 1.0 mm and 62.0 μm provide food availability and facilitate escape from predators. In a study on the caridean prawn Crangon septemspinosa (Decapoda, Crangonidae), Oullette et al (2003) also found that this species preferred finer substrates, and connected this choice with survival, since C. septemspinosa lives much of its life cycle on this type of substrate. This finding agrees with our observation that M. brasiliense individuals spent most of their time buried in this type of substrate.…”
Section: Discussionmentioning
confidence: 95%
“…Even though these animals live in a different environment and consequently differ physiologically from the species studied in this present study, both results confirm the statement by Dall et al (1990) that substrates with particles between 1.0 mm and 62.0 μm provide food availability and facilitate escape from predators. In a study on the caridean prawn Crangon septemspinosa (Decapoda, Crangonidae), Oullette et al (2003) also found that this species preferred finer substrates, and connected this choice with survival, since C. septemspinosa lives much of its life cycle on this type of substrate. This finding agrees with our observation that M. brasiliense individuals spent most of their time buried in this type of substrate.…”
Section: Discussionmentioning
confidence: 95%
“…Entre os principais fatores que influenciam o comportamento dos camarões estão: disponibilidade de alimento, mecanismos relacionados à escavação e aspectos associados à respiração quando enterrados. A maioria dos camarões marinhos utiliza a escavação e o enterramento como estratégia de fuga e refúgio (Dall et al, 1990;Oullette et al, 2003;Freire et al, 2011). O tipo de substrato deve permitir a expressão natural desses comportamentos, o que favorece o conforto ambiental para o animal.…”
Section: Resultsunclassified
“…Kenyon et al (1995) não observaram preferência de juvenis de P. monodon em relação aos substratos mais finos. Já Oullette et al (2003) verificaram que Cragon septemspinosa prefere areia em detrimento de substratos artificiais, o que sugere que fatores físicos, como granulometria do substrato (tamanho do grão e porosidade), são reconhecidos pelos camarões.…”
Section: Resultsunclassified
See 1 more Smart Citation
“…They burrow into substrates for protection from predators and to ambush passing prey (Minello et al., 1987), an activity which can be affected by the nature and size of sediment particles (Trueman and Ansell, 1969; Ruello, 1973; Moller and Jones, 1975; Aziz and Greenwood, 1982; Pinn and Ansell, 1993). Observations in our laboratory showed that when offered a choice, sand shrimp display a strong preference for a sand substrate over a peat substrate and showed difficulty burrowing completely into the peat substrate (Ouellette et al., 2003). Furthermore, sand shrimp are known to ingest substrate particles during foraging (Wilcox and Jeffries, 1974), a phenomenon also observed during our laboratory experiments (Ouellette et al., 2003).…”
Section: Introductionmentioning
confidence: 99%